Pengaruh Pengaruh kompetensi pedagogik guru dan pembelajaran berbasis proyek terhadap keterampilan menulis cerita peserta didik kelas V pada mata pelajaran bahasa indonesia di SDN Gugus 1 Selaparang: kompetensi pedagogik guru, pembelajaran berbasis proyek, keterampilan menulis cerita - Aminah, siti aminah; Aminah, Siti; Asrin; Astria, Fitri Puji (LITPAM, 2025)
This study aims to determine the effect of teachers’ pedagogical competence and project-based learning on the story- writing skills of fifth-grade students in Bahasa Indonesia at SDN Gugus 1 Selaparang. The research was conducted at SDN 5 Mataram and SDN 18 Mataram, which are part of Gugus 1 Selaparang. This study employed a quantitative method with an ex-post facto design. The sample consisted of students from Class VB at SDN 5 Mataram and Class V at SDN 18 Mataram, selected using purposive sampling. Data were collected through questionnaires to measure teachers’ pedagogical competence and the implementation of project- based learning, as well as a writing test to assess students’ story-writing skills. The data were analyzed using simple and multiple linear regression. The results showed that teachers’ pedagogical competence had a significant effect on students’ story- writing skills, with a t-value of 2.683 > 2.019 and a significance level of 0.010 < 0.05. Project-based learning also had a significant effect, with a t-value of 2.342 > 2.019 and a significance level of 0.024 < 0.05. Furthermore, teachers’ pedagogical competence and project-based learning simultaneously had a significant effect on students’ story-writing skills, indicated by an F-value of 6.650 > 3.23 and a significance level of 0.003 < 0.05.